Targeting defective sphingosine kinase 1 in Niemann-Pick type C disease with an activator mitigates cholesterol accumulation - Newton, Jason; Palladino, Elisa N D; Weigel, Cynthia; Maceyka, Michael; Gräler, Markus H; Senkal, Can E; Enriz, Ricardo D; Marvanova, Pavlina; Jampilek, Josef; Lima, Santiago; Milstien, Sheldon; Spiegel, Sarah (The Journal of biological chemistry, 2020)
Niemann-Pick type C (NPC) disease is a lysosomal storage disorder arising from mutations in the cholesterol-trafficking protein NPC1 (95%) or NPC2 (5%). These mutations result in accumulation of low-density lipoprotein-derived cholesterol in late endosomes/lysosomes, disruption of endocytic trafficking, and stalled autophagic flux. Additionally, NPC disease results in sphingolipid accumulation, yet it is unique among the sphingolipidoses because of the absence of mutations in the enzymes responsible for sphingolipid degradation. In this work, we examined the cause for sphingosine and sphingolipid accumulation in multiple cellular models of NPC disease and observed that the activity of sphingosine kinase 1 (SphK1), one of the two isoenzymes that phosphorylate sphingoid bases, was markedly reduced in both NPC1 mutant and NPC1 knockout cells. Conversely, SphK1 inhibition with the isotype-specific inhibitor SK1-I in WT cells induced accumulation of cholesterol and reduced cholesterol esterification. Of note, a novel SphK1 activator (SK1-A) that we have characterized decreased sphingoid base and complex sphingolipid accumulation and ameliorated autophagic defects in both NPC1 mutant and NPC1 knockout cells. Remarkably, in these cells, SK1-A also reduced cholesterol accumulation and increased cholesterol ester formation. Our results indicate that a SphK1 activator rescues aberrant cholesterol and sphingolipid storage and trafficking in NPC1 mutant cells. These observations highlight a previously unknown link between SphK1 activity, NPC1, and cholesterol trafficking and metabolism.
Keywords: NPC1; Cell Line; sphingosine-1-phosphate (S1P); Lysosomes; endozomy; Vesicular Transport Proteins; neurodegeneration; transport proteinů; Niemann-Pick Disease, Type C; fosfotransferasy s alkoholovou skupinou jako akceptorem; sphingosine kinase; Primary Cell Culture; Carrier Proteins; Cholesterol Esters; sfingolipidy; Phosphotransferases (Alcohol Group Acceptor); membránové glykoproteiny; Mice; Intracellular Signaling Peptides and Proteins; primární buněčná kultura; sphingolipids; Cholesterol; estery cholesterolu; lipid metabolism; Sphingosine; protein NPC1; cholesterol; Membrane Glycoproteins; sfingosin; intracelulární signální peptidy a proteiny; zvířata; Humans; lysosomal storage disease; Niemannova-Pickova nemoc typu C; Fibroblasts; Niemann–Pick type C; genetic disorder; lyzozomy; myši; Protein Transport; sphingolipid; sphingosine kinase (SphK); Sphingolipids; buněčné linie; Endosomes; Niemann-Pick C1 Protein; transportní proteiny; lidé; vezikulární transportní proteiny; fibroblasty; Animals